The cis‐regulatory effect of an Alzheimer's disease‐associated poly‐T locus on expression of TOMM40 and apolipoprotein E genes. Issue 5 (17th January 2014) - Linnertz, Colton; Anderson, Lauren; Gottschalk, William; Crenshaw, Donna; Lutz, Michael W.; Allen, Jawara; Saith, Sunita; Mihovilovic, Mirta; Burke, James R.; Welsh‐Bohmer, Kathleen A.; Roses, Allen D.; Chiba‐Falek, Ornit
Abstract: Background: We investigated the genomic region spanning the Translocase of the Outer Mitochondrial Membrane 40‐kD ( TOMM40 ) and Apolipoprotein E ( APOE ) genes, that has been associated with the risk and age of onset of late‐onset Alzheimer's disease (LOAD) to determine whether a highly polymorphic, intronic poly‐T within this region (rs10524523; hereafter, 523) affects expression of the APOE and TOMM40 genes. Alleles of this locus are classified as S, short; L, long; and VL, very long based on the number of T residues. Methods: We evaluated differences in APOE messenger RNA (mRNA) and TOMM40 mRNA levels as a function of the 523 genotype in two brain regions from APOE ε3/ε3 white autopsy‐confirmed LOAD cases and normal controls. We further investigated the effect of the 523 locus in its native genomic context using a luciferase expression system. Results: The expression of both genes was significantly increased with disease. Mean expression of APOE and TOMM40 mRNA levels were higher in VL homozygotes compared with S homozygotes in the temporal and occipital cortexes from normal and LOAD cases. Results of a luciferase reporter system were consistent with the human brain mRNA analysis; the 523 VL poly‐T resulted in significantly higher expression than the S poly‐T. Although the effect of poly‐T length on reporter expression was the same in HepG2 hepatoma and SH‐SY5Y neuroblastoma cells, the magnitude of the effect was greater in the neuroblastoma than in the hepatoma cells, which implies tissue‐specific modulation of the 523 poly‐T. Conclusions: These results suggest that the 523 locus may contribute to LOAD susceptibility by modulating the expression of TOMM40 and/or APOE transcription.